2009
DOI: 10.1007/s11626-009-9192-7
|View full text |Cite
|
Sign up to set email alerts
|

Developing a novel serum-free cell culture model of skeletal muscle differentiation by systematically studying the role of different growth factors in myotube formation

Abstract: This work describes the step-by-step development of a novel, serum-free, in vitro cell culture system resulting in the formation of robust, contracting, multinucleate myotubes from dissociated skeletal muscle cells obtained from the hind limbs of fetal rats. This defined system consisted of a serum-free medium formulation developed by the systematic addition of different growth factors as well as a non-biological, cell growth promoting substrate, N-1[3-(trimethoxysilyl) propyl] diethylenetriamine (DETA). Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…The starting medium formulation, surface modification and plating technique was developed previously by our lab to create a system for the development of myotubes derived from embryonic E18 rat hind‐limbs . However, this system was insufficient to enable the development of myotubes from satellite cells isolated from the TA of adult rats.…”
Section: Resultsmentioning
confidence: 99%
“…The starting medium formulation, surface modification and plating technique was developed previously by our lab to create a system for the development of myotubes derived from embryonic E18 rat hind‐limbs . However, this system was insufficient to enable the development of myotubes from satellite cells isolated from the TA of adult rats.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the undefined nature of animal sera, the effect of novel therapeutics may be confounded by the inclusion of such additives in the culture medium. Serum-free media formulations are available for both rodent and human skeletal muscle cultures 1821 and provide a more controlled, well defined environment for performing compound assessment. Similarly, the use of biological coatings (collagen, laminin etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, transforming growth factor (TGF)-β treatment has been shown to improve peak twitch and tetanic contractile activity, as well as sarcomere development and organization, in scaffold-free engineered skeletal muscle tissues [74]. Studies have also investigated the addition of a variety of neuronal growth factors to muscle cultures, and demonstrated that such supplementation can significantly enhance myotube differentiation and sarcomeric development in cultured skeletal muscle cells [75]. …”
Section: Tissue Engineering Approaches For Generating Skeletal Musclementioning
confidence: 99%
“…Studies have shown that combining electrical stimulation with mechanical strain improves skeletal muscle maturation over and above what is achievable with either stimulus alone [29, 110]. Similarly, studies into the sequential addition of multiple growth factors describe the increased benefit of supplementation to cultures of skeletal muscle myotubes [75]. Likewise, the addition of neuronal factors has been shown to promote the spontaneous contractile activity of cultured human myotubes, and a lack of contraction is observed when these factors are omitted [111].…”
Section: Current Limitations and Future Perspectivesmentioning
confidence: 99%